Challenges and actions to the environmental management of Bio-Medical Waste during COVID-19 pandemic in India. Issue 3 (March 2021) - Goswami, Mrinalini; Goswami, Pranjal J.; Nautiyal, Sunil; Prakash, Satya
Abstract: The outbreak of COVID-19 has engendered a global health crisis along with diverse impacts on economy, society and environment. Efforts to combat this pandemic have also significantly shot-up the quantity of Bio-medical Waste (BMW) generation. Safe disposal of large quantity of BMW has been gradually posing a major challenge. BMW management is mostly implemented at municipal level following regulatory guidelines defined by respective states and the Union. This article is a narrative of the status of BMW generation, management and regulation in India in the context of COVID-19 crisis. The article is based on comparative analysis of data on BMW generation and management from authentic sources, a systematic literature review and review of news reports. In the current pandemic situation where media has been playing a significant role in highlighting all the concerns related to COVID-19 spread and management. Assessing the ground situation regarding effectiveness of prevailing BMW management facilities, requirement and suggestions can provide insights to the subject with policy implications for India and countries as well. The discussion has been built on different dimensions of BMW management during the pandemic including existing infrastructures, capacity utilisation, policy guidelines, operational practices and waste-handlers aspects. The results on state-wise analysis of reported BMW quantity and active COVID-19 patients also reveal some non-linear relationship between the two variables. Delhi, the National Capital is situated at a better position in terms of BMW management as compared to other studied states. The findings are expected to provide valuable insights to the policy makers and other relevant authorities to evaluate adequateness as well as efficiency quotients of entire BMW management landscape. Some of the critical observations of this article are also expected to offer impetus for enhancing national disaster preparedness in future. Abstract : BMW; Healthcare waste; Safe disposal; Environmental health; Waste management regulations